Workers of the World: Essays Toward a Global Labor History - Palmer, Bryan D. (Labour / Le Travail, 2010)
The article reviews the book, "Workers of the World: Essays Toward a Global Labor History" by Marcel van der Linden.
Keywords: BOOKS -- Reviews; History; Labor; Nonfiction; VAN der Linden, Marcel; WORKERS of the World: Essays Toward a Global Labor History (Book)